Geology, Geochemistry and Structural Analysis of the Basement Rocks of Gora Area, Part of Keffi Sheet 208 NE, Northcentral Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The basement complex rock that underlies Gora and its surroundings consistsprimarily of banded and porphyroblastic gneisses, biotite schist, and the minor rocksbeing pegmatites and quartzo-feldspatic veins. This study aims to characterize, at a1:25,000 scale, the geology, structure, and geochemistry of the rock units in theGora region. To attain this aim, field research, petrographic, and geochemicalstudies were conducted. Quartz, feldspars, biotite, and hornblende were identifiedas major minerals in petrographic analyses of the gneiss, with muscovite and apatitepresent in trace amounts. X-ray fluorescence (XRF) analytical methods were usedto determine the rocks' geochemical compositions. Fold, fault, pinch, and swell, andvein sizes were all quantified. Major fractures, joints, and veins all run NW-SE,while smaller ones run NE-SW. The structural NW-SE and NE-SW trends are alsoreflected in the data that has been linearly analysed (SRTM DEM). The geochemicalresults obtained revealed that the gneisses and biotite schist are high-K calc-alkalineand orthogneiss derived from igneous protoliths. The gneisses and biotite schistwere further classified on the SiO2 vs. FeOt /MgO binary diagram in calc-alkalineseries. The gneisses and biotite schist are peraluminous in nature. The gneisses andbiotite schist were formed in a passive continental margin tectonic setting.